Editorial - Rajbhandari, Mani Man Singh (SXC Journal, 2026)
Dear Reader,It is our pleasure to announce the publication of SXC Journal’s Volume 3, 2026. It has been a remarkable academic and scientific journey to bring the SXC Journal to this stage by integrating multidisciplinary areas. This volume includes articles from management, the social sciences, education, and science to reflect a multidisciplinary platform. This provides academics and readers with easy access to download the published articles. It also benefits students by providing free access to the articles. Our published articles and volumes will be available in the NepJol journal index on the St. Xavier’s College website under the research category.  Our next volume will be published in 2027, and we invite academics, writers, scientists, scholars, and others to submit their articles. All articles will undergo blind peer review to uphold academic integrity. Articles published in the SXC journal will also undergo a plagiarism check to ensure the trustworthiness of the research.The invitation to submit articles for the next volume in 2027 is open to all. Last but not least, we would like to thank all the authors and reviewers who contributed to the successful publication of volume 3, 2026.Thank you.Best regards,Mani Man Singh Rajbhandari, PhDAssociate EditorSXC JournalSt. Xavier’s College, Maitighar, Kathmandu, Nepal